Effects of Ferric Oxyhydroxide on Anaerobic Microbial Dechlorination of Polychlorinated Biphenyls in Hudson and Grasse River Sediment Microcosms: Dechlorination Extent, Preferences, Ortho Removal, and Its Enhancement - Xu, Yan; Gregory, Kelvin B.; VanBriesen, Jeanne M. (Frontiers in Microbiology, 2018)
Microbial reductive dechlorination of polychlorinated biphenyls (PCBs) has been observed in many PCB-impacted sediments. However, this biodegradation is relatively site-specific and can be affected by PCB compositions and sediment geochemical conditions. To better understand the influence of a common competing electron acceptor, ferric oxyhyroxide (FeOOH), on dechlorination, two sediments (Hudson River and Grasse River sediments), and two PCB mixtures (PCB 5/12, 64/71, 105/114 and 149/153/170 in Mixture 1 and PCB 5/12, 64/71, 82/97/99, 144/170 in Mixture 2) were used for this microcosm study. The addition of 40 mmole/kg FeOOH completely inhibited PCB dechlorination in the Hudson sediment, but only moderately inhibited PCB dechlorination in the Grasse sediment with a 3-week longer lag time. The inhibitory effect in the Grasse sediment was mainly due to the loss of unflanked para dechlorination activity. Fe(II) analysis showed that dechlorination started prior to the consumption of Fe(III), which indicates PCB reduction and Fe(III) reduction were able to take place concurrently. Dehalococcoides 16S rRNA genes increased with the commencement of dechlorination in the Grasse sediment, but not in the completely inhibited Hudson sediment. Rare ortho dechlorination pathways were identified in FeOOH-amended Grasse sediment microcosms, dominated by transformations of PCB 25(24-3-CB) to PCB 13(3-4-CB) and PCB 28(24-4-CB) to PCB 15(4-4-CB). The addition of carbon sources (acetate or a fatty acid mixture with acetate, propionate and butyrate) after 27 weeks of incubation reinitiated dechlorination in FeOOH-amended Hudson sediment microcosms. Also, the addition of carbon sources greatly enhanced ortho dechlorination in FeOOH-amended Grasse microcosms, indicating the utilization of acetate and/or the fatty acid mixture for ortho dechlorination related microorganisms. A dechlorination pathway analysis approach revealed that para-flanked meta dechlorination was primarily preferred followed by ortho-/double-flanked meta dechlorination and single-/double-flanked para dechlorination in the Grasse sediment.